NEW GEOCHEMICAL DATA OF BASALTS IN THE TSOROIDOG AREA, CENTRAL MONGOLIA - T. Oyunchimeg; L. Dagva-Ochir; D. Otgonbaatar; A. Battushig; B. Enkhdalai (Геодинамика и тектонофизика, 2017)
At present, geochemical data are widely used for reconstructing geodynamic settings, especially, volcanic rocks of mafic composition, i.e., basalts, because they are widespread in many orogenic belts and are indicative of different geodynamic environments. In general, we propose the reconstruction of the tectonic settings of basalts according to their relationships with associated ocean plate stratigraphy (OPS) sediments, their petrogenesis and their geochemical features.